2016
DOI: 10.3390/vaccines4040043
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Chemotherapy, Radiation and Epigenetic Modifiers in Cancer Cell Expression of Immune Inhibitory and Stimulatory Molecules and Anti-Tumor Efficacy

Abstract: Genomic destabilizers, such as radiation and chemotherapy, and epigenetic modifiers are used for the treatment of cancer due to their apoptotic effects on the aberrant cells. However, these therapies may also induce widespread changes within the immune system and cancer cells, which may enable tumors to avoid immune surveillance and escape from host anti-tumor immunity. Genomic destabilizers can induce immunogenic death of tumor cells, but also induce upregulation of immune inhibitory ligands on drug-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 171 publications
(233 reference statements)
0
21
0
Order By: Relevance
“…Unlike in ovarian cancer patients, lung cancer patients with a high level of PD‐1 had relatively poor OS and FPS after chemotherapy treatment, which implied that a combination of chemotherapy and PD‐1 blockade might produce unexpected benefits. It has already been proven that chemotherapy can change the expression level of PD‐1, but the direction of this change depends on the cell line and chemotherapeutic agent . Moreover, a recent study investigated the expression of PD‐1 and PD‐L1 before and after platinum‐based neoadjuvant chemotherapy in lung cancer patients and found that only PD‐L1 expression decreased significantly after chemotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in ovarian cancer patients, lung cancer patients with a high level of PD‐1 had relatively poor OS and FPS after chemotherapy treatment, which implied that a combination of chemotherapy and PD‐1 blockade might produce unexpected benefits. It has already been proven that chemotherapy can change the expression level of PD‐1, but the direction of this change depends on the cell line and chemotherapeutic agent . Moreover, a recent study investigated the expression of PD‐1 and PD‐L1 before and after platinum‐based neoadjuvant chemotherapy in lung cancer patients and found that only PD‐L1 expression decreased significantly after chemotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…4,16 DAMPs expressed in the tumor cells induced by the destructive effects of chemotherapy or radiotherapy can be followed by antigen-specific cytotoxic T cell killing. 17,18 In the present study, the combination of adjuvant chemotherapy and radiotherapy contributed to immunogenicity.…”
Section: Pre-operative Peripheral Lymphocyte Count Correlated With mentioning
confidence: 99%
“…In cases of DNA hypermethylation, therapy with DNA methyltransferase inhibitors (DNMTi) such as azacytidine and decitabine restores the expression of HLA class I derived peptide complex [ 263 ]. Azacytidine increased the transcription of APM genes and HLA class I molecule expression in lung carcinoma and melanoma cells [ 246 , 247 ]. Guadecitabine, a novel DNMTi, significantly up-regulated both basal and IFN-γ-dependent expression of HLA class I derived peptide complex in breast cancer cells [ 248 ].…”
Section: Restoring Hla Class I Expression As a Novel Therapeutic Smentioning
confidence: 99%